Increased Cardiac Workload in the Upright Posture in Men: Noninvasive Hemodynamics in Men Versus Women. Issue 6 (June 2016) - Kangas, Pauliina; Tahvanainen, Anna; Tikkakoski, Antti; Koskela, Jenni; Uitto, Marko; Viik, Jari; Kähönen, Mika; Kööbi, Tiit; Mustonen, Jukka; Pörsti, Ilkka
Abstract : Background: Men and women differ in the risk of cardiovascular disease, but the underlying mechanisms are not completely understood. We examined possible sex‐related differences in supine and upright cardiovascular regulation. Methods and Results: Hemodynamics were recorded from 167 men and 167 women of matching age (≈45 years) and body mass index (≈26.5) during passive head‐up tilt. None had diabetes mellitus or cardiovascular disease other than hypertension or used antihypertensive medication. Whole‐body impedance cardiography, tonometric radial blood pressure, and heart rate variability were analyzed. Results were adjusted for height, smoking, alcohol intake, mean arterial pressure, plasma lipids, and glucose. Supine hemodynamic differences were minor: Men had lower heart rate (−4%) and higher stroke index (+7.5%) than women ( P <0.05 for both). Upright systemic vascular resistance was lower (−10%), but stroke index (+15%), cardiac index (+16%), and left cardiac work were clearly higher (+20%) in men than in women ( P <0.001 for all). Corresponding results were observed in a subgroup of men and postmenopausal women (n=76, aged >55 years). Heart rate variability analyses showed higher low:high frequency ratios in supine ( P <0.001) and upright ( P =0.003) positions in men. Conclusions: The foremost difference in cardiovascular regulation between sexes was higher upright hemodynamic workload for the heart in men, a finding not explained by known cardiovascular risk factors or hormonal differences before menopause. Heart rate variability analyses indicated higher sympathovagal balance in men regardless of body position. The deviations in upright hemodynamics could play a role in the differences in cardiovascular risk between men and women. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01742702.